Finite Element Modelling and Parametric Studies of Semi-Closed Thin-Walled Steel Polygonal Columns For The Application on Steel Lattice Towers - Ryan, Bona; Koltsakis, Efthymios; Manoleas, Panagiotis (UI Scholars Hub, 2019)
The trend of structural engineering in the recent years is toward the use of lighter and more economical structural elements. In steel construction, peculiarly, main structural member composed by thin-walled elements are being explored by researchers due to their potential to offer better solution with economical features. However, the use of slender profiles and a complex cross sections shape lead to requirements to study instability phenomenon in a form of local, distortional, flexural, torsional and coupled instability. Such complex structural behaviour is inevitably accompanied by demand to improve calculation methods and design provisions. In this context an innovative solution of structural element composed of thin-walled plates is proposed for the application on lattice support structure of wind turbine. A semi-closed section is made by assembling series of folded plates into polygonal profiles with mechanical fasteners, loaded in compression and bending moment which occurs as the effect of forces acting on the connection. The expected structural behaviour of the column is a mixture between the open and closed cross-section. These cases will be investigated through numerical analysis and parametric studies of the proposed profiles for the investigation of buckling behaviour and ultimate resistance, respectively.